(untitled) (Journal of the College of Basic Education, 2022)
The problem of this research lies in the fact that some contemporary transactions are marred by some disputes and disagreements between the parties to the contract, and the reason for this problem is the lack of understanding between the two parties by the rule of the mortgage guarantee, so this research aims to highlight the rule of the mortgage guarantee according to the four schools of thought. In this research, the researcher followed the inductive approach, by extrapolating the sayings of the jurists on this issue and presenting their evidence, then the comparative approach, which relies on weighting between opinions and weighting between evidence and choosing the most correct opinion. At the end of the research, the researcher reached several conclusions, the most important of which is that if the mortgage perishes in the hands of the mortgagee, if its value and the debt are whether it perishes with it, and if its value is less, the pledgee returns to the pledgor with what remains of the debt, and if it is more, the pledgee returns to the pledgee for what has increased, this The opinion of Malik and Abu Hanifa, and Al-Shafi’i and Ahmad disagreed with it.